Non‐Invasive In Situ Dynamic Monitoring of Elastic Properties of Composite Battery Electrodes by EQCM‐D1. (27th April 2015) - Shpigel, Netanel; Levi, Mikhael D.; Sigalov, Sergey; Girshevitz, Olga; Aurbach, Doron; Daikhin, Leonid; Jäckel, Nicolas; Presser, Volker
Abstract Reversible Li‐ion intercalation into composite Li‐ion battery (LIB) electrodes is often accompanied by significant dimensional electrode changes (deformation) resulting in significant deterioration of the cycling performance. Viscoelastic properties of polymeric binders affected by intercalation‐induced deformation of composite LIB electrodes have never been probed in situ on operating electrochemical cells. Here, we introduce a newly developed noninvasive method, namely electrochemical quartz‐crystal microbalance with dissipation monitoring (EQCM‐D), for in situ monitoring of elastic properties of polymeric binders during charging of LIB electrodes. As such, we find EQCM‐D as a uniquely suitable tool to track the binder's structural rigidity/softness in composite Li insertion electrodes in real‐time by the characteristic increase/decrease of the dissipation factor during the charging–discharging process. The binders partially swollen in aprotic solutions demonstrate intermediate viscoelastic charge‐rate‐dependent behavior, revealing rigid/soft behavior at high/low charging rates, respectively. The method can be adjusted for continuous monitoring of elastic properties of the polymeric binders over the entire LIB electrodes cycling life.